Zachowania zdrowotne młodzieży licealnej w doświadczaniu choroby = Health behaviors of secondary-school youth in experiencing disease - Kozłowska, Ewelina; Kowalczyk, Anna; Marzec, Agnieszka (Journal of Education, Health and Sport, 2015)
Kozłowska Ewelina, Kowalczyk Anna, Marzec Agnieszka. Zachowania zdrowotne młodzieży licealnej w doświadczaniu choroby = Health behaviors of secondary-school youth in experiencing disease. Journal of Education, Health and Sport. 2015;5(5):243-252. ISSN 2391-8306. DOI 10.5281/zenodo.17649 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A243-252 https://pbn.nauka.gov.pl/works/560180 http://dx.doi.org/10.5281/zenodo.17649 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.04.2015. Accepted: 08.05.2015. Zachowania zdrowotne młodzieży licealnej w doświadczaniu choroby Health behaviors of secondary-school youth in experiencing disease Ewelina Kozłowska1(a,b,c,d,e), Anna Kowalczyk2(d,e), Agnieszka Marzec3(a,f) 1Samodzielna Pracownia Epidemiologii, Uniwersytet Medyczny w Lublinie 2Studenckie Koło Naukowe przy Katedrze Zdrowia Publicznego, Uniwersytet Medyczny w Lublinie 3Zakład Dietetyki Klinicznej, Uniwersytet Medyczny w Lubinie (a) koncepcja badań (b) zebranie materiału do badań (c) analiza statystyczna (d) opracowanie tekstu (e) opracowanie piśmiennictwa (f) merytoryczny nadzór nad ostateczną wersją artykułu Publikacja finansowana ze środków własnych autorów. Adres do korespondencji/ Adress for correspondence Mgr Ewelina Kozłowska Samodzielna Pracownia Epidemiologii, Uniwersytet Medyczny w Lublinie ul. Chodźki 1, 20-093 Lublin tel. 517760214 e-mail: ewelina.kozlowska@umlub.pl Streszczenie Wprowadzenie i cel pracy: Sposób reagowania od chwili dostrzeżenia przez chorego pierwszych oznak nieprawidłowości w funkcjonowaniu swojego organizmu może istotnie wpływać na przebieg choroby i niejednokrotnie przesądzać o możliwości skutecznego powrotu do zdrowia. Celem przeprowadzonej analizy było poznanie zachowań zdrowotnych młodzieży licealnej w obliczu obserwowanych symptomów choroby. Materiał i metoda: Przeprowadzono badanie ankietowe wśród 174 uczniów II Liceum Ogólnokształcącego im. Marii Konopnickiej w Zamościu. Zastosowano metodę sondażu diagnostycznego z wykorzystaniem autorskiego kwestionariusza ankiety. Zgromadzony materiał badawczy poddano analizie statystycznej nieparametrycznym testem statystycznym χ2 Pearsona. Dla wnioskowania statystycznego przyjęto poziom istotności 0,05 Wyniki: Blisko połowa badanych (47%) zgłasza zauważone objawy po paru dniach, tygodniu lub dopiero w ostateczności, gdy stają się zbyt uciążliwe. Ankietowani zwlekają z powiadomieniem o nich z nadzieją, że same ustąpią (61%), ze względu na brak czasu rodziców i lekceważenie przez nich płynących sygnałów (19%) oraz w celu uniknięcia wizyt u lekarza (16%). Aż 72% uczniów ukrywa przed rodzicami, opiekunami lub lekarzem zauważone oznaki choroby. Wnioski: Licealiści doświadczając dolegliwości zdrowotnych związanych z rozwijającym się procesem chorobowym wykazują liczne zachowania o charakterze bionegatywnym. Istnieje potrzeba wdrożenia w szkołach działań ukierunkowanych na wzrost udziału zajęć z zakresu edukacji zdrowotnej. Kształtowanie wśród młodzieży właściwych postaw zdrowotnych, nabywanie wiedzy i umiejętności z zakresu profilaktyki chorób to najistotniejsze elementy nowoczesnej medycyny szkolnej. Słowa kluczowe: zachowania zdrowotne, objawy chorobowe, prewencja wtórna, młodzież licealna. Abstract Introduction and work aim: Reaction from the moment of noticing by the sick person of first irregularity symptoms in body function can significantly affect the course of disease and often forejudge about possible successful recovery. An aim of conducted analysis was to study the health behaviors of secondary-school youth in face of observed disease symptoms. Material and Method: Diagnostic survey was conducted amongst 174 students of the secondary school from Zamość. The diagnostic survey was an applied method with a use of author’s questionnaire form. Obtained material was subjected to statistical analysis with nonparametric Pearson’s test χ2. For statistical inference the significance level of < 0.05 was adopted. Results: Nearly half of respondents (47%) reported observed symptoms after a few days, week or only as a last resort, when they become too troublesome. Respondents drag off with notifying about them in a hope that they alone will go away (61%), due to lack of parent’s time and disregard of signals (19%), as well as in order to avoid visits at the doctor (16%). As much as 72% of students hide disease symptoms before their parents, careers or the doctor. Conclusions: Secondary-school students experiencing medical problems associated with developing pathological process show numerous of behaviors about bio-negative character. There is a need to implement in schools activities aimed to increase the participation in health education classes. Development of appropriate health attitudes among young people, acquisition of knowledge and skills from prevention scope is the most important elements of modern medicine school. Keywords: health behaviors, symptoms, secondary prevention, secondary-school youth.